Cervical Biomechanics and Neck Pain of “Head-Spinning” Breakdancers - Kauther, M. D.; Piotrowski, M.; Hussmann, B.; Lendemans, S.; Wedemeyer, C.; Jaeger, M. (International Journal of Sports Medicine, 2014)
The cervical spine of breakdancers is at great risk due to reversed body loading during headspin manoeuvers. This study focused on the cervical biomechanics of breakdancers and a correlation with neck pain. A standardized interview and biomechanical testing of the cervical spine of 25 participants with “headspin” ability ages 16–34 years and an age-matched cohort of 25 participants without any cervical spine problems was conducted. Neck pain history, Neck Disability Index (NDI), cervical range of motion (CROM) and cervical torque were recorded. The “headspin” group reported significantly better subjective fitness, more cervical complaints, higher pain intensity, a longer history of neck pain and a worse NDI compared to the “normal” collective. The “headspin” group showed a 2–2.5 times higher rate of neck pain than the normal population, with increased cervical flexion (p<0.05) and increased cervical torque in all planes (p<0.001). The CROM showed a negative moderate to strong correlation with NDI, pain intensity and history of neck pain. Sports medicine practitioners should be aware of headspin maneuver accidents that pose the risk of fractures, dislocations and spinal cord injuries of breakdancers.
Keywords: breakdance; spine; torque; CROM; power move